Experimental investigation of the flow in a micro-channelled combustor and its relation to flame behaviour - Gupta,A; Qadri,UA; Koutita,K; Zadrazil,I; Hussain,T; Balachandran,R; Markides,CN (Experimental Thermal and Fluid Science, 2020)
The dynamic behaviour of periodic laminar premixed acetylene-air flames in a micro-channelled combustor consisting of an array of five planar rectangular channels was found to be influenced by the equiv- alence ratio and flow-rate of the continuously and steadily injected premixed fuel charge. Three distinct flame stages were observed — planar, chaotic and trident, which were strongly correlated to the flow dynamics. The effect of the flow on the flame behaviour was investigated by characterizing the cold flow in a scaled-up model channel with the same aspect ratio as the combustion micro-channel. Direct flow visualization using flow tracers and quantitative velocity-field data from PIV measurements showed both an increase in the bottom recircula- tion zone reattachment length (along the floor of the channel) and a decrease in the lateral recirculation zone reattachment length (along the sides of the channel) with increasing flow Reynolds number. Comparison of the flow and flame transition locations downstream of the injection point suggested that the location of trident flame onset coincides with the flow bottom recirculation zone reattachment length. The planar-chaotic flame transition location was observed to be influenced by the homogeneity of the mixture downstream of the injection plane.